Perancangan Sistem Informasi Pembukuan Pada Vape Store Kopi Vape Berbasis Web - Robo, Salahudin; Subekti, Ryan Tri; Pratama, Wahyuda Putra; Nazir, Fahrul; Trisno, T (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
Established in 2022, kopi vape is a vape shop in Jayapura, located in the Papua province. Despite being a modern store, kopi vape's financial bookkeeping system is handled manually. This method is not systematic nor computerized and presents several weaknesses. Transactions are still recorded manually through books, then inputted one-by-one via Microsoft Excel. Issues related to this process include errors in inputting transaction data, slow transaction recording, and even data loss. Using UML, the waterfall approach progresses through communication, design, modeling, construction, and deployment, culminating in the system flow design - an interface blueprint of sorts. Using a systematic and computerized information system for bookkeeping results in a more efficient process for finding documents quickly and accurately. This method minimizes common errors in manual recording, such as mistakes in counting, recording, adjusting data, and forgetting to record transactions.